On Being Included : Racism and Diversity in Institutional Life - Ahmed, Sara, 1969- (Book collections on Project MUSE., 2012)
Ahmed argues that a commitment to diversity is frequently substituted for a commitment to actual change. She traces the work that diversity does, examining how the term is used and the way it serves to make questions about racism seem impertinent. Her study is based in universities and her research is primarily in the UK and Australia, but the argument is equally valid in North America and beyond.